Creatividad y resiliencia. Análisis comparativo de nuevas formas de inserción creativa en contextos de incertidumbre y complejidad - Quiñones Rodríguez, María Aracelly (Revista Científica, 2012)
Human mobility, a common characteristic in the history mankind, accentuated in the recent decades by multiple factors, is approached in this article in two contexts and specific populations and dissimilar groups, including Colombian and Ecuatorian immigrants in Spain and people in conditions of forced displacement in Bogotá, D.C. Creativity, like constructive possibility of human being is analyzed to the contexts of uncertainty and complexity that are doomed to a voluntary or imposed, who make up the sample in the investigation.